MIDIALIZAÇÕES OBJETIVADAS E VULNERABILIDADES DAS INFÂNCIAS - Lúcia Lacerda dos Anjos (2022)
In the present dissertation, we problematized about the influences of digital media regarding children in the context of the cultural industry, since we understand entertainment as a business branch disseminated as mass culture by online platforms, for example. It is in this environment that we locate the studies that point to children as a social construction inserted in historical, economic, political and cultural contexts as agents (subjects of action). According to this definition, our general goal was to analyze what kind of childhoods are propagated in three youtubers channels. Our central question becomes, what are the possible childhoods that these channels promote? What conceptions of childhoods or ways of being a child are suggested by these channels is our main question. The methodology chosen was qualitative and quantitative research with a documental instrument on the internet, of classical ethnographic inspiration (dense description) and online ethnography or ethnography in cyberspace (field), on the YouTubeplatform as a field of interaction of children (content and viewer). The observation criteria of the three channels followed the following order for each channel: the first video released; the three most popular, that is, the ones with the highest number of subscriptions and views, and the last one released, the most recent video published up to the time of the research (December 2021). The theoretical framework is anchored in Critical Theory of Society, especially in the writings of Theodor Adorno and his contemporary commentators, and in childhood studies. Our conclusions indicate the need to deepen such reflections, since the three channels analyzed are conducted by the children's parents, and that the children are often prevented from manifesting themselves spontaneously, since they follow scripts pre-established by the channels' organizers. The comments were excluded from the channels by determination of the platform. This procedure demarcates a restriction that turns children into mere spectators of the show, reducing them to subscriptions and likes, which sets up what we call the medialization of childhoods. That is, registered viewers who leave likes, making the mirin celebrities executors of content an extension of the tentacles of the cultural industry. Keywords: Culture Industry. Digital Medias. YouTube. Childhoods.